Patterns of recurrence and outcomes of poor responders to neoadjuvant long-course chemoradiotherapy for rectal cancer - Yang, Yufei; Luo, Dakui; Ding, Weiji; Li, Qingguo; Li, Xinxiang (Journal of Gastrointestinal Oncology; Vol 17, No 2 (April 30, 2026): Journal of Gastrointestinal Oncology, 2026)
Neoadjuvant chemoradiotherapy (nCRT) followed by surgery and adjuvant chemotherapy is a standard therapy for locally advanced rectal cancer (LARC). However, a significant proportion of patients exhibit a poor response, and few studies focus on this subgroup’s prognosis.